Diagnóstico da pesquisa em biodiversidade no Brasil - Joly, Carlos A.; Haddad, Celio Fernando Baptista [UNESP]; Verdade, L. M.; Oliveira, Mariana Cabral da; Bolzani, Vanderlan da Silva [UNESP]; Berlinck, Roberto G. S. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2011)
Biodiversity is a result of millions of years of biological evolution, and is the component of the system which supports life on our planet. Besides the intrinsic value of each species, all of them as a whole, as well as of the interactions among the species, and their interaction with the physical and chemical environment, result in ecosystem services vital for supporting life on Earth. Because of that, the science of biodiversity is largely recognized as a priority area of scientific investigation both in developed and developing countries. In Brazil, the research on biodiversity can be divided in three parts: 1) discovery and characterization of biodiversity – including marine and human-altered landscapes – systematics and taxonomy; 2) understanding the functioning of ecosystems and environmental services, including in marine and human-altered landscapes; 3) bioprospecting of the chemical diversity of the Brazilian biota.

A biodiversidade resulta de milhões de anos de evolução biológica e é o componente do sistema de suporte à vida de nosso planeta. Além do valor intrínseco de cada espécie, seu conjunto, bem como o de interações entre espécies e destas com o meio físico-químico, resultam em serviços ecossistêmicos imprescindíveis para manter a vida na Terra. Sendo assim, a ciência da biodiversidade é amplamente reconhecida como área prioritária de investigação científica, tanto nos países desenvolvidos como naqueles em desenvolvimento. No Brasil, a pesquisa em biodiversidade pode ser dividida em três principais vertentes: 1) descoberta e caracterização da biodiversidade, inclusive marinha e em paisagens alteradas – sistemática e taxonomia; 2) compreensão do funcionamento de ecossistemas e serviços ambientais, inclusive marinhos e em paisagens alteradas; 3) bioprospecção da quimiodiversidade da biota brasileira.
Keywords: Biodiversidade; Coleções biológicas; Repatriação eletrônica; Biodiversity; Biological collections; Electronic repatriation